Counteracting Social Exclusion of People with Motor Dysfunctions through Physical Culture- Opinions of People with and without Physical Disabilities - Marzena Grzybowska; Wojciech J. Cynarski; Grzegorz Błażejewski (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2017)
In the years 2010-2012, the research survey was carried out on 480 people with or without physical disabilities. The aim of the research was to obtain information on attitudes and opinions of people with physical disabilities towards the possibility of reducing social marginalization through participation in physical culture. The research confirmed that the respondents' attitudes towards participation of those people in physical culture were, in majority, positive. Participants of the research expressed the opinion that the feeling of marginalization of physically disabled persons would not have been so strong if there had been the possibility of an active participation in sport, recreation and tourism as well as in active rehabilitation. The possibilities of an active participation in physical activity should be inexpensive and widely accessible regardless of the year season and with providing volunteer assistance and transport facilitations.